EKSISTENSI BAHASA INDONESIA DALAM PENDIDIKAN BERBASIS KERAGAMAN BUDAYA - Zamzani Zamzani (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Language as a means and a cultural product. Language activities cannot be separated from the activities of thinking with a specific cultural framework. The view point that human beings cannot think without language, strenghten the existence of language as a means of culture when thinking is seen as part of the spiritual culture. Humans as homo symbolicum 'the creature who use the symbol' whose scope is broader than homo sapiens 'thinking beings.' In the context of Indonesia—who shows diversity, the diversity in many aspects—the existence of Indonesian language in the diversity of language and local culture in Indonesia has become an important topic to be questioned. When associated with education in Indonesia, Indonesian language has a central role in the development of intellectual, social, and emotional of learners and the supporting success in all of fields of study, in addition to the role of regional languages which cannot be ignored.